Interactions of transcranial magnetic stimulation with brain oscillations: a narrative review - Wang, Qijun; Gong, Anjuan; Feng, Zhen; Bai, Yang; Ziemann, Ulf (Frontiers in Systems Neuroscience, 2024)
Brain responses to transcranial magnetic stimulation (TMS) can be recorded with electroencephalography (EEG) and comprise TMS-evoked potentials and TMS-induced oscillations. Repetitive TMS may entrain endogenous brain oscillations. In turn, ongoing brain oscillations prior to the TMS pulse can influence the effects of the TMS pulse. These intricate TMS-EEG and EEG-TMS interactions are increasingly attracting the interest of researchers and clinicians. This review surveys the literature of TMS and its interactions with brain oscillations as measured by EEG in health and disease.